Socialization of bag composter in producing artificial compost for the community - Putra Bismantolo; Hendri Hestiawan; Dewi Sartika (Dharmakayana, 2024)
Waste management must be the responsibility of citizens and the government. The government's task is to activate citizen participation up to household level by having sufficient knowledge e.g. socialization of 3R concept (Reduce, Reuse, Recycle) in handling the waste. The Reduce is about the impact of waste on life by that the community minimizes the use of goods that can produce waste. The reuse concept is about to utilize waste for other uses. The Recycle is about to recycle the waste to other goods e.g. by composting to produce fertilizer in a small space, simple equipment, and very low costs. Compost production by using a composter bag sprayed by composter fluid is called as the artificial compost. To introduce the system to the community, the training on how to make deal with it is pursued in RT.33 RW.8, Sawah Lebar Village, Bengkulu City, involving the local administrators and housewives. The method is learning by doing under supervising of a community service team of the Engineering Faculty Universitas Bengkulu.